Advancements in complement inhibition for PNH and primary complement–mediated thrombotic microangiopathy - Thalia Padilla Kelley; Hannah King; Aditya Malhotra; Thomas G. DeLoughery; Kylee Martens; Joseph J. Shatzel (Blood Advances, 2025)
Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) and primary complement–mediated thrombotic microangiopathy, also known as atypical hemolytic uremic syndrome (aHUS), are hematologic disorders characterized by dysregulation of the complement system leading to hemolysis and other systemic and potentially lethal complications. The advent of C5 inhibition with agents such as eculizumab and ravulizumab has revolutionized the management of patients with these disorders, although some may still experience clinically significant breakthrough extravascular hemolysis. Over the past several years, novel therapies targeting upstream pathways of complement inhibition have been approved for the treatment of patients with PNH experiencing breakthrough hemolysis despite C5 inhibition. These agents currently include pegcetacoplan, a C3 inhibitor; iptacopan, an oral factor B inhibitor; danicopan, an oral factor D inhibitor; and crovalimab, an anti-C5 monoclonal antibody. This review highlights recent advances in complement-targeted therapies for PNH, including their indications and efficacy and safety data from key randomized trials. In addition, we review current data supporting the use of these novel agents for aHUS, for which only the terminal complement inhibitors eculizumab and ravulizumab are currently approved. Future research is crucial to establish the long-term efficacy and safety profiles of these novel therapies, ensuring the best treatment strategies for patients with PNH and aHUS.